2017
DOI: 10.1371/journal.pone.0176481
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of MRSA and ESBL among asylum seekers in the Netherlands

Abstract: Migration is one of the risk factors for the spread of multidrug-resistant organisms (MDRO). The increasing influx of migrants challenges local health care systems. To provide evidence for both hospital hygiene measure and empirical antibiotic therapy, we analysed all cultures performed in asylum seekers between January 1st 2014 and December 31st 2015 for methicillin resistant Staphylococcus aureus (MRSA) and for multidrug-resistant Enterobacteriaceae (MDRE). We compared these with cultures from the Dutch pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
26
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 16 publications
10
26
3
Order By: Relevance
“…The MRSA carriage rate among newcomers in this study was 16.9%, which was higher than that found in refugees who were already in camps, as well as that in the host community, although the difference was not statistically significant. These results are in agreement with MRSA prevalence rates in refugees residing in asylum centers or camps in Switzerland (15.7%) (Piso et al, 2017), Italy (12.5%) (Angeletti et al, 2016), and the Netherlands (approximately 10%) (Ravensbergen et al, 2017). However, the prevalence rates of MRSA in both the host community and refugees in the present study were much higher than those in the population of the Netherlands as a whole (1%), as well as those of Germany (10%), Belgium (0%), and Iceland (0%) (Abbara et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The MRSA carriage rate among newcomers in this study was 16.9%, which was higher than that found in refugees who were already in camps, as well as that in the host community, although the difference was not statistically significant. These results are in agreement with MRSA prevalence rates in refugees residing in asylum centers or camps in Switzerland (15.7%) (Piso et al, 2017), Italy (12.5%) (Angeletti et al, 2016), and the Netherlands (approximately 10%) (Ravensbergen et al, 2017). However, the prevalence rates of MRSA in both the host community and refugees in the present study were much higher than those in the population of the Netherlands as a whole (1%), as well as those of Germany (10%), Belgium (0%), and Iceland (0%) (Abbara et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…However, the prevalence rates of MRSA in both the host community and refugees in the present study were much higher than those in the population of the Netherlands as a whole (1%), as well as those of Germany (10%), Belgium (0%), and Iceland (0%) (Abbara et al, 2018). In contrast, MRSA prevalence rates among refugees in the current study were lower than the rates of up to 37-56% found in Greece, Portugal (Ravensbergen et al, 2017), and Romania (Abbara et al, 2018;Ravensbergen et al, 2017). These figures raise serious concerns that movement of refugees to lowprevalence countries might result in the spread of MRSA in the new communities.…”
Section: Discussioncontrasting
confidence: 86%
“…In developing countries facing high rates of internal displacements, there is an urgent need to unify screenings and treatments, and to fight the as yet largely unaddressed problem of counterfeit medicines. In the more developed destination countries, screening of migrant populations seeking healthcare may also help to understand and control the inter-country spread of antibiotic resistance [ 61 ]. Health assessment on arrival is a useful way of gaining an initial understanding of the health of incident migrant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance may be considered an emerging infectious disease, and is clearly linked to human mobility [ 84 , 85 ]. Prevalence of carriage of methicillin-resistant Staphylococcus aureus and multi-drug resistant Enterobacteriaceae in migrant populations may be as high as 27% [ 61 , 85 87 ]. Migrants are also overrepresented in terms of multi-drug resistant tuberculosis compared to host populations [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation